PENGARUH SOSIODEMOGRAFI RESPONDEN KOTA DENPASAR TERHADAP PERILAKU PENGGUNAAN OBAT SAAT MENJALANI ISOLASI MANDIRI COVID-19 - Ni Putu Sinthya Devi Widyarini; Ni Nyoman Dwi Sutrisnawati; Ni Putu Aryati Suryaningsih (Bali International Scientific Forum, 2021)
Abstract Background: COVID-19 is global pandemic with a very fast rate of spread. As of June 2021, Bali Province experienced 110% increase in the number of weekly cases. The sharp increase caused referrals to self-isolation also increase. The increase in COVID-19 self-isolation referrals has also increased trend of diverse drug use behaviors by the community. Differences in sociodemographic between communities are considered to affect the behavior of drug use formed while undergoing COVID-19 self-isolation, so that a study of the correlation is needed. Purpose: This study aims to determine the sociodemographic influence respondents of Denpasar City on drug use behavior formed while undergoing COVID-19 self-isolation. Methods: The research design used is descriptive quantitative with a cross sectional design. The number of samples used is as many as 96 respondents by purposive sampling. Measurements were carried out using questionnaires with Data Analysis Techniques of Binner Logistics Regression Multivariate and Univariate. Results: The sociodemographic of Denpasar City community involved in being respondents has mostly been married 57.29%, aged between 26-45 years 51.04%, female 55.21%, private employees 37.50%, education of high school 55.21% and high income 55.21%. Denpasar City respondents mostly found have positive drug use behavior (52.08%). Respondents' last education level (OR= 4,685), income (OR= 5,112), age (OR= 2,794) and occupation (OR= 1,763) had a significant influence (p=0.001-0.029). Conclusion: People in Denpasar City who have undergone COVID-19 self-isolation are classified having positive drug use behavior. Respondents' age, education level, income and occupation had significant influence on drug use behavior while undergoing COVID-19 self-isolation. Keyword: COVID-19, Drug Use Behavior, Self-Isolation, Sociodemographic